Tìm đạo hàm của hàm số \(y=\dfrac{-2x^2+x-7}{x^2+3}\).
![]() | \(y'=\dfrac{-3x^2-13x-10}{\left(x^2+3\right)^2}\) |
![]() | \(y'=\dfrac{-x^2+x+3}{\left(x^2+3\right)^2}\) |
![]() | \(y'=\dfrac{-x^2+2x+3}{\left(x^2+3\right)^2}\) |
![]() | \(y'=\dfrac{-7x^2-13x-10}{\left(x^2+3\right)^2}\) |
Chọn phương án C.
\(\begin{aligned}
y'&=\dfrac{\left(-2x^2+x-7\right)'\left(x^2+3\right)-\left(-2x^2+x-7\right)\left(x^2+3\right)'}{\left(x^2+3\right)^2}\\
&=\dfrac{\left(-4x+1\right)\left(x^2+3\right)-\left(-2x^2+x-7\right)\left(2x\right)}{\left(x^2+3\right)^2}\\
&=\dfrac{\left(-4x^3-12x+x^2+3\right)-\left(-4x^3+2x^2-14x\right)}{\left(x^2+3\right)^2}\\
&=\dfrac{-x^2+2x+3}{\left(x^2+3\right)^2}.
\end{aligned}\)